MD simulation study of direct permeation of a nanoparticle across the cell membrane under an external electric field. Issue 23 (31st May 2016) - Shimizu, Kenta; Nakamura, Hideya; Watano, Satoru
Abstract : When a specific range of electric field was applied, the NP directly permeated across a lipid bilayer without membrane wrapping of the NP as well as without the disruption of the membrane after the permeation. Abstract : Nanoparticles (NPs) have been attracting much attention for biomedical and pharmaceutical applications. In most of the applications, NPs are required to translocate across the cell membrane and to reach the cell cytosol. Experimental studies have reported that by applying an electric field NPs can directly permeate across the cell membrane without the confinement of NPs by endocytic vesicles. However, damage to the cell can often be a concern. Understanding of the mechanism underlying the direct permeation of NPs under an external electric field can greatly contribute to the realization of a technology for the direct delivery of NPs. Here we investigated the permeation of a cationic gold NP across a phospholipid bilayer under an external electric field using a coarse-grained molecular dynamics simulation. When an external electric field that is equal to the membrane breakdown intensity was applied, a typical NP delivery by electroporation was shown: the cationic gold NP directly permeated across a lipid bilayer without membrane wrapping of the NP, while a persistent transmembrane pore was formed. However, when a specific range of the electric field that is lower than the membrane breakdown intensity was applied, a unique permeation pathway was exhibited: the generated transmembrane pore immediately resealed after the direct permeation of NP. Furthermore, we found that the affinity of the NP for the membrane surface is a key for the self-resealing of the pore. Our finding suggests that by applying an electric field in a suitable range NPs can be directly delivered into the cell with less cellular damage.